Comparison of Perceived and Technical Healthcare Quality in Primary Health Facilities: Implications for a Sustainable National Health Insurance Scheme in Ghana. - Robert Kaba Alhassan (PLoS ONE, 2015)
BACKGROUND:Quality care in health facilities is critical for a sustainable health insurance system because of its influence on clients' decisions to participate in health insurance and utilize health services. Exploration of the different dimensions of healthcare quality and their associations will help determine more effective quality improvement interventions and health insurance sustainability strategies, especially in resource constrained countries in Africa where universal access to good quality care remains a challenge. PURPOSE:To examine the differences in perceptions of clients and health staff on quality healthcare and determine if these perceptions are associated with technical quality proxies in health facilities. Implications of the findings for a sustainable National Health Insurance Scheme (NHIS) in Ghana are also discussed. METHODS:This is a cross-sectional study in two southern regions in Ghana involving 64 primary health facilities: 1,903 households and 324 health staff. Data collection lasted from March to June, 2012. A Wilcoxon-Mann-Whitney test was performed to determine differences in client and health staff perceptions of quality healthcare. Spearman's rank correlation test was used to ascertain associations between perceived and technical quality care proxies in health facilities, and ordered logistic regression employed to predict the determinants of client and staff-perceived quality healthcare. RESULTS:Negative association was found between technical quality and client-perceived quality care (coef. = -0.0991, p<0.0001). Significant staff-client perception differences were found in all healthcare quality proxies, suggesting some level of unbalanced commitment to quality improvement and potential information asymmetry between clients and service providers. Overall, the findings suggest that increased efforts towards technical quality care alone will not necessarily translate into better client-perceived quality care and willingness to utilize health services in NHIS-accredited health facilities. CONCLUSION:There is the need to intensify client education and balanced commitment to technical and perceived quality improvement efforts. This will help enhance client confidence in Ghana's healthcare system, stimulate active participation in the national health insurance, increase healthcare utilization and ultimately improve public health outcomes.